CLASSIFICATION OF GAZ-PUMPING EQUIPMENT’S REFUSES TYPES ON THE COMPRESSOR STATIONS DK UKRTRANSGAZ - Матвієнко, Роман Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Determination is given to the types of stops of rocking gas aggregates over, the analysis of reasons of origin of refusals of equipment of the compressor stations is conducted, the graphic diagrams of distributing of refusals are built, the particle of the forced stops GPA is expected among the common amount of all stops for current period